Coordinated europium ion-based post-modified ZIF-8 fluorescent composite material as well as preparation method and application thereof
By preparing a ZIF-8 fluorescent composite material based on coordinated europium ion post-modification, the problems of insufficient stability of rare earth ions and complexity of water detection were solved, achieving high sensitivity and high stability for the detection of Co2+ and thiamethoxam, which is suitable for environmental and life science fields.
Patent Information
- Application Number
- CN202511067677.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-11-07
AI Technical Summary
The lack of stability of rare earth ions such as Eu3+ in existing technologies limits their practical application in fluorescence sensing, and the detection methods for new pollutants in water, such as Co2+ and thiamethoxam, are complex and have high detection limits.
By preparing a ZIF-8 fluorescent composite material based on coordinated europium ion post-modification, zinc nitrate was used to form a ZIF-8-NH2 framework with 2-methylimidazole and 2-aminobenzimidazole, and europium nitrate and terephthalic acid were introduced to enhance the loading stability and luminescence efficiency of Eu3+, which was then used to detect Co2+ and thiamethoxam in water.
High stability and high sensitivity detection of Eu@ZIF-8-NH2 material were achieved, with detection limits of 0.127 μmol·L⁻¹ and 0.0934 μmol·L⁻¹, respectively. It has good anti-interference ability and fast response, and is suitable for water detection in environmental and life science fields.
Smart Images

Figure CN120904474A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of biological medicine, and particularly relates to a coordination europium ion-based post-modified ZIF-8 fluorescent composite material. BACKGROUND
[0002] Improper use exacerbates the problem of water scarcity, and the world is facing the challenge of water shortage. In addition, toxic and harmful environmental pollutants are flowing into groundwater, rivers and oceans, causing water quality damage. Drinking or using these contaminated water resources will have a direct or indirect impact on human health.
[0003] The main toxic pollutants in water bodies include organic dyes, pharmaceuticals and personal care products, heavy metal ions, fertilizers and pesticides, etc. In recent years, one of them, a harmful substance called emerging pollutants, has attracted particular attention, including pesticides, endocrine disruptors, antibiotics, drinking water disinfection by-products, perfluorinated compounds and microplastics. Emerging pollutants have more serious potential hazards than ordinary pollutants, and most of them are persistent organic pollutants with a wide range of sources. The detection and removal of these pollutants are complex, so the treatment of emerging pollutants in water bodies worldwide is urgent.
[0004] After the Yaghi group reported the first MOFs material, in the past three decades, a large number of MOFs have been constructed by changing organic ligands, metal ions and synthesis methods, greatly enriching the structural diversity of MOFs and expanding the applications of MOFs. MOFs have unique structures and properties: (1) structural units and framework structures, with tunability and diversity; (2) high porosity and specific surface area; (3) size can be easily controlled, providing the possibility for practical application. Therefore, since MOFs were reported, they have attracted the attention of many researchers. At present, they have excellent performance in gas storage, adsorption separation, catalytic biomimetics, drug delivery, analysis and sensing. Among them, zeolitic imidazolate framework (ZIF-8) has become an ideal carrier for encapsulating functional materials, such as quantum dots (QDS) or rare earth elements, to construct multifunctional composites due to its excellent chemical stability and pore structure.
[0005] Rare earth ions have the advantages of high quantum yield and narrow emission peak in fluorescence sensing due to their unique electronic transition characteristics, but their insufficient stability limits practical application. SUMMARY
[0006] The purpose of the present application is to overcome the shortcomings of the prior art, and to provide an ester compound, a diaryl acrylic acid mixture, a preparation method and an application thereof.
[0007] One of the technical solutions adopted by the present application to solve its technical problems is:
[0008] A preparation method of a coordination Eu ion post-modified ZIF-8 fluorescent composite material, the method comprising:
[0009] S1: Dissolve zinc nitrate hexahydrate, 2-methyl imidazole and 2-amino benzimidazole in methanol to form solution A and solution B respectively, after ultrasonic treatment, quickly add solution B to solution A and stir, stir at room temperature for 4h, then centrifugal wash with methanol, dry in a blast drying oven at 55-65℃ for 11-13h, then transfer to a vacuum drying oven at 140-160℃ and activate for 11-13h, then grind to obtain an amino functionalized ZIF-8 composite material;
[0010] S2: Dissolve the amino functionalized ZIF-8 composite material obtained in step S1 and europium nitrate hexahydrate in methanol, then add terephthalic acid, stir at room temperature for 5-7h, centrifugal process, wash with methanol, dry in a blast drying oven at 55-65℃ for 24h, then grind to obtain the coordination Eu ion post-modified ZIF-8 fluorescent composite material.
[0011] Further, in the step S1, the molar mass ratio of 2-methyl imidazole and 2-amino benzimidazole is 54:1.
[0012] Further, in the step S1, the molar mass ratio of Zn 2+ , 2-methyl imidazole and 2-amino benzimidazole is 10:50-55:1-1.5.
[0013] Further, in the step S2, the mass ratio of Eu 3+ and the amino functionalized ZIF-8 composite material is 1:2.5-3.
[0014] Further, in the step S2, the molar ratio of Eu 3+ and terephthalic acid is 2:3.
[0015] Further, in the step S2, the mass ratio of the terephthalic acid and the amino functionalized ZIF-8 composite material is 5-5.5:1.
[0016] The second technical solution adopted by the present application to solve its technical problems is:
[0017] A coordination Eu ion post-modified ZIF-8 fluorescent composite material, which is prepared by the above-mentioned preparation method of the coordination Eu ion post-modified ZIF-8 fluorescent composite material.
[0018] The third technical solution adopted by the present application to solve its technical problems is:
[0019] An application of a ZIF-8 fluorescent composite material post-modified with coordinated europium ions in water detection, wherein the ZIF-8 fluorescent composite material post-modified with coordinated europium ions is used to detect Co-containing substances. 2+ Water bodies containing thiamethoxam.
[0020] Furthermore, the ZIF-8 fluorescent composite material modified with coordinated europium ions was dispersed in an ethanol solution and ultrasonically treated to obtain a uniformly dispersed suspension.
[0021] Furthermore, the concentration of the ZIF-8 fluorescent composite material modified with coordinated europium ions is 0.5 mg / mL.
[0022] Compared with the prior art, this technical solution has the following advantages:
[0023] This invention uses zinc nitrate and 2-methylimidazolium-2-aminobenzimidazole to form a porous ZIF-8-NH2 framework through coordination bonds, and then introduces europium nitrate and phthalic acid as auxiliary ligands. 3+ It can coordinate with the carboxyl group (-COOH) of phthalic acid. Simultaneously, it can bind to the amino group of ZIF-8-NH2 through coordination, enhancing the Eu... 3+ The loading stability; in addition, terephthalic acid can act as a "sensitizer" to improve Eu 3+ To improve luminescence efficiency, Eu@ZIF-8-NH2 fluorescent material was prepared and applied to the detection of metal ions and organic matter in water. Results showed that the synthesized Eu@ZIF-8-NH2 exhibited rare-earth europium fluorescence characteristics, emitting red fluorescence; Co... 2+ Thiamethoxam has a quenching effect on its fluorescence at an excitation wavelength of 254 nm and a probe concentration of 0.5 mg / mL. -1 A fluorescence detection method for the two substances mentioned above was established, and Co was obtained. 2+ The linear concentration ranges for thiamethoxam and thiamethoxam are 0–203 μmol·L⁻¹ and 0–112 μmol·L⁻¹, respectively, with detection limits of 0.127 μmol·L⁻¹ and 0.0934 μmol·L⁻¹, respectively. This detection method exhibits low detection limits, high sensitivity, and strong anti-interference capabilities, showing promising application prospects in environmental and life science fields. Attached Figure Description
[0024] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0025] Figure 1SEM characterization graphs of ZIF-8, ZIF-8-NH2, Eu@ZIF-8-NH2, (a) is the morphology graph of ZIF-8 under 2 μm scale, (b) is the SEM graph of ZIF-8 under 4 μm scale, (c) is the morphology graph of ZIF-8-NH2 under 400 nm scale, (d) is the SEM graph of ZIF-8-NH2 under 200 nm scale, (e) is the morphology graph of Eu@ZIF-8-NH2 under 500 nm scale, (f) is the morphology graph of Eu@ZIF-8-NH2 under 1 μm scale;
[0026] Figure 2 Elemental distribution graph and EDS graph of Eu@ZIF-8-NH2;
[0027] Figure 3 Elemental distribution graph and EDS graph of ZIF-8-NH2;
[0028] Figure 4 XRD diffraction spectrum of ZIF-8, ZIF-8-NH2, Eu@ZIF-8-NH2;
[0029] Figure 5 FT-IR graph of ZIF-8, ZIF-8-NH2, Eu@ZIF-8-NH2;
[0030] Figure 6 Thermogravimetric graph of ZIF-8-NH2;
[0031] Figure 7 Thermogravimetric graph of Eu@ZIF-8-NH2;
[0032] Figure 8 N2 adsorption desorption isotherm of ZIF-8, ZIF-8-NH2, Eu@ZIF-8-NH2;
[0033] Figure 9 Pore size distribution graph of ZIF-8, ZIF-8-NH2, Eu@ZIF-8-NH2;
[0034] Figure 10 Fluorescence spectrum graph of Eu@ZIF-8-NH2 under different excitation wavelengths;
[0035] Figure 11 Fluorescence spectrum graph of Eu@ZIF-8-NH2 within 0-7d;
[0036] Figure 12 Fluorescence spectrum graph of Eu@ZIF-8-NH2 under different concentrations;
[0037] Figure 13Figure for comparison of fluorescence intensity of Eu@ZIF-8-NH2 in different solvents;
[0038] Figure 14 Figure for comparison of fluorescence intensity of Eu@ZIF-8-NH2 after adding Co 2+ and thiamethoxam at different pH values;
[0039] Figure 15 Figure for response time of Eu@ZIF-8-NH2 after adding Co 2+
[0040] Figure 16 Figure for response time of Eu@ZIF-8-NH2 after adding thiamethoxam;
[0041] Figure 17 Figure for comparison of fluorescence intensity of Eu@ZIF-8-NH2 under different Co 2+ concentrations;
[0042] Figure 18 Figure for comparison of fluorescence intensity of Eu@ZIF-8-NH2 under different thiamethoxam concentrations;
[0043] Figure 19 Figure for linear fitting of Co 2+ titration Stern-Volmer equation;
[0044] Figure 20 Figure for linear fitting of THI titration Stern-Volmer equation;
[0045] Figure 21 Figure for selectivity test of Eu@ZIF-8-NH2;
[0046] Figure 22 Figure for anti-interference test of Eu@ZIF-8-NH2. DETAILED DESCRIPTION
[0047] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the scope of protection of the present application.
[0048] The experimental reagents used in the present embodiment are shown in Table 1.
[0049] Table 1 Experimental reagents
[0050]
[0051]
[0052] The experimental instruments used in this embodiment are shown in Table 2.
[0053] Table 2 Experimental instruments
[0054]
[0055] Example 1: Preparation of melamine-based covalent organic framework
[0056] 2.0550 g of 2-methylimidazole was weighed and dissolved in 50 mL of methanol, and 0.745 g of zinc nitrate hexahydrate was also weighed and dissolved in 50 mL of methanol, the two solutions were mixed, a constant temperature water bath was used for continuous stirring at 50°C for 2 h, then methanol was used for centrifugal washing 3 times to remove unreacted raw materials, the centrifugal speed was 8000 rpm / min, and after drying in a blast drying oven at 60°C for 24 h, grinding was performed to obtain a white powder, which was a zeolitic imidazolate framework material, denoted as ZIF-8, for subsequent performance characterization and application research.
[0057] Example 2: Preparation of amino-functionalized ZIF-8 composite material
[0058] 1.4688 g of zinc nitrate hexahydrate was weighed and dissolved in 50 mL of methanol to form solution A, 2.1886 g of 2-methylimidazole and 0.0668 g of 2-aminobenzimidazole were weighed and dissolved in 50 mL of methanol to form solution B, after ultrasonic treatment for 5 min, the B solution was quickly added to solution A and stirred, and stirring was performed at room temperature for 4 h, then methanol was used for centrifugal washing 3 times to remove unreacted raw materials, the centrifugal speed was 8000 rpm / min, and after drying in a blast drying oven at 60°C for 12 h, the material was transferred to a vacuum drying oven at 150°C for activation for 12 h, and then grinding was performed to obtain an amino-functionalized ZIF-8 composite material, denoted as ZIF-8-NH2, for subsequent fluorescence sensing performance research.
[0059] Example 3: Preparation of coordination Eu ion-based post-modified ZIF-8 fluorescent composite material
[0060] 133.8 mg of europium nitrate hexahydrate and 398.6 mg of the ZIF-8-NH2 prepared in Example 2 were weighed and dissolved in 100 mL of methanol, and 74.7 mg of terephthalic acid was weighed and added to the above mixed solution, stirring was performed at room temperature for 6 h, then methanol was used for centrifugal washing 3 times to remove unreacted impurities, the centrifugal speed was 8000 rpm / min, and after drying in a blast drying oven at 60°C for 24 h, grinding was performed to obtain a white powder, which was a coordination Eu ion-based post-modified ZIF-8 fluorescent composite material, denoted as Eu@ZIF-8-NH2, for subsequent fluorescence sensing performance research.
[0061] In order to understand the composition and structure of each sample, X-ray diffraction analyzer (XRD), Fourier transform infrared spectrometer (FT-IR), scanning electron microscope (SEM), ultraviolet / visible spectrophotometer, thermal gravimetric analyzer (TG) and the like are used for corresponding characterization of the sample.
[0062] Test Example 1: Scanning Electron Microscope and Energy Dispersive Spectroscopy (SEM-EDS)
[0063] In this experiment, scanning electron microscope is used to perform morphology characterization analysis of the prepared sample, and X-ray energy spectrometer (EDS) is used to perform element distribution, qualitative and semi-quantitative analysis of the surface of the sample. The specific operation steps are as follows: the conductive glue is pasted on the sample stage, then a small amount of the sample to be tested after drying treatment is dipped on the conductive glue with a toothpick, and after 2 min of gold spraying treatment, the test is performed, and finally the material is subjected to face scanning and point scanning for energy spectrum analysis. The acceleration voltage is set to 10-15KV, and the acceleration current is set to 10-15μA.
[0064] SEM is used to detect the morphology characteristics of the prepared ZIF-8, ZIF-8-NH2 and Eu@ZIF-8-NH2. As shown in Figure 1 , ZIF-8 and ZIF-8-NH2 are both dodecahedron morphology, and the particle size is about 70nm. By loading Eu 3+ and terephthalic acid ligand on the outer surface of ZIF-8-NH2, Eu@ZIF-8-NH2 is formed, and the size is slightly larger than that of ZIF-8-NH2. Because the outer surface is coated with rare earth elements and ligands, the morphology also changes slightly. The element distribution of Eu@ZIF-8-NH2 and ZIF-8-NH2 is analyzed by EDS energy spectrum as shown in Figure 2 、 3 As shown in the results, the main elements of the prepared Eu@ZIF-8-NH2 are C, N, O, Zn and Eu.
[0065] Test Example 2: X-ray Diffraction Analysis (XRD)
[0066] X-ray diffractometer is used to perform phase characterization analysis of the prepared material. The specific operation steps are as follows: the dried sample is uniformly placed on the glass slide and compacted for detection, and the scanning speed is set to 2° / min, and the scanning 2θ range is 2-80°.
[0067] The XRD diffraction spectrum of ZIF-8, ZIF-8-NH2 and Eu@ZIF-8-NH2 is tested to explore the crystal structure characteristics of the material. As shown in Figure 4As shown, the diffraction peaks of ZIF-8 at 7.4°, 12.7°, 14.7°, 16.5° and 18° are attributed to the characteristic crystal faces of (011), (112), (022), (013) and (222) of ZIF-8 crystal, respectively, which are consistent with the reported in the literature, indicating the synthesis of pure phase crystal. The diffraction peaks of ZIF-8-NH2 are basically consistent with those of ZIF-8, indicating that the structure of ZIF-8 is not destroyed during the amination process. The above characteristic diffraction peaks are also observed in the XRD spectrum of Eu@ZIF-8-NH2, indicating that the structural characteristics of the material are retained after loading.
[0068] Test Example 3: Fourier Transform Infrared Spectroscopy Analysis (FT-IR)
[0069] Fourier Transform Infrared Spectroscopy (FT-IR) is a kind of effective functional group identification instrument, which uses infrared light of a certain wave number range to irradiate the sample, part of the infrared light is absorbed by the sample and converted into rotational or vibrational energy, showing a certain range of frequency spectrum signals. In this experiment, Fourier Transform Infrared Spectrometer was used for functional group characterization analysis of the material. The specific operation steps are as follows: a small amount of sample after drying treatment is placed in a marquis mask for careful grinding, then the instrument is blank corrected, after correction, the ground sample is placed on the test mold table of the infrared spectrometer, and the scanning range is set to 400-4000 cm -1 .
[0070] The FT-IR spectrum of the sample was tested, as shown in Figure 5 , Eu@ZIF-8-NH2 showed a vibration peak of C=N bond stretching on the imidazole ring at 1579 cm -1 , the metal-ligand bond vibration absorption peak near 520 cm -1 , the peaks at 1150 cm -1 and 996 cm -1 were produced by C-N single bond in ZIF-8, the characteristic peaks at 754 cm -1 and 688 cm -1 were produced by the imidazole ring in ZIF-8, the peak at 3410 cm -1 was the peak of amino group, the peak at 1680 cm -1 was the carbonyl stretching vibration peak of p-xylyl, indicating that there was p-phthalic acid coordination.
[0071] Test Example 4: Thermogravimetric Analysis (TG)
[0072] Thermogravimetric analysis is used to analyze the thermal degradation process of the material. This method can be used to study the thermal stability, decomposition and combustion heat of the sample. The specific operation steps are as follows: a small amount of sample treated by drying is placed in a crucible for testing, and the temperature is set to 30-1000℃, and the heating rate is 30℃ / min. By analyzing the thermogravimetric determination results of the material, the weight loss temperature of the material under the heating condition can be deduced, and the information of the skeleton decomposition can be obtained, and the stability of the material can be judged.
[0073] Figure 6 The thermogravimetric analysis of ZIF-8-NH2 shows that the stability of ZIF-8-NH2 is good, and the structure begins to decompose at about 600℃. Figure 7 It is shown that the mass loss of Eu@ZIF-8-NH2 in the range of 40-980℃ can be divided into two stages. The mass loss in the first stage (40-458℃) is 7%, mainly due to the evaporation of water and methanol in the sample channel; the mass loss in the second stage (458-980℃) is 49%, which means that the sample has undergone decomposition, volatilization and other changes in this range, and the structure of the sample has been destroyed and the skeleton has collapsed. In addition, the carbon residue rate of the sample is 93% at 458℃; the carbon residue rate of the sample is about 44% at 980℃, indicating that the synthesized sample has good stability.
[0074] Test Example 5: Full-automatic specific surface area adsorption analysis (BET)
[0075] The specific surface area of the sample is usually calculated by nitrogen adsorption-desorption method (BET). The principle of this method is to cool the solid sample to low temperature under vacuum condition, then gradually add nitrogen as adsorption filler, measure the nitrogen adsorption amount after the relative pressure (P / P0) is balanced, and finally calculate the specific surface area by BET equation. In this experiment, a specific surface area adsorption instrument was used to analyze the specific surface area and pore structure of the prepared sample. The specific operation steps are as follows: take a small amount of sample (0.10-0.15g) treated by drying, place it at the bottom of the container, and then perform vacuum drying and degassing (200℃ / 2h).
[0076] Figure 8 The results of nitrogen adsorption-desorption isotherm test on the sample are used to determine the specific surface area of the sample. The specific surface area of ZIF-8 is 1545.37m 2 ·g -1 , the specific surface area of ZIF-8-NH2 is 1188.04m 2 ·g -1 , and the specific surface area of Eu@ZIF-8-NH2 is 1071.29m 2 ·g -1 ; the pore volume is 0.59cm 3 ·g -1, the average pore size is 2.20 nm. In contrast, the specific surface area of Eu@ZIF-8-NH2 is less than that of ZIF-8-NH2, indicating that the loading of Eu 3+ does not significantly reduce the specific surface area of ZIF-8-NH2.
[0077] Test Example 6: Analysis of fluorescence properties and detection conditions optimization
[0078] A certain concentration of the fluorescent probe dispersion was prepared, and then the optimal excitation light, emission light, and fluorescence source of the fluorescent properties were characterized by a molecular fluorescence spectrometer. The stability, optimal solvent conditions, and optimal pH were optimized.
[0079] A fluorescence spectrometer (FL) is a spectroscopic analysis technique. Since all fluorescent substances have their own unique fluorescence properties, they can be used as qualitative and quantitative instruments. In this experiment, a fluorescence spectrometer was used to characterize and analyze the optical properties of the prepared materials, and a specific pollutant was quantitatively analyzed according to the fluorescence spectrophotometric method. The specific operation steps are as follows: a small amount of the sample to be tested was diluted to a specific concentration and placed in a light-transmitting glass cuvette for testing. The light source scanning wavelength was set to 300-800 nm or a specific light excitation and emission wavelength.
[0080] Figure 10 The fluorescence intensity of Eu@ZIF-8-NH2 at each wavelength in the range of 240 nm to 270 nm was detected, and the fluorescence intensity of the sample solution under the excitation wavelength of 254 nm was the strongest. Good fluorescence stability is a prerequisite for the application of fluorescent probe materials in practice, so the fluorescence stability of Eu@ZIF-8-NH2 was detected within 0-7 days, as shown in Figure 11 , it can be clearly observed that the fluorescence intensity does not show a decay trend within this time range, and the fluorescence intensity remains stable.
[0081] Before the fluorescence titration experiment, in order to improve the detection sensitivity, the pH conditions, optimal concentration, solvent environment, and response time of Eu@ZIF-8-NH2 for detecting Co 2+ and thiamethoxam were optimized. Figure 12 The change in fluorescence intensity of Eu@ZIF-8-NH2 under different concentrations can be clearly seen, and the fluorescence intensity is the strongest at a concentration of 0.5 mg·mL -1 , so the optimal concentration of the probe solution is determined to be 0.5 mg·mL -1 . Figure 13 The fluorescence intensity of Eu@ZIF-8-NH2 in water, ethanol, methanol, acetonitrile, and N,N-dimethylformamide (DMF) under different solvents, so it can be seen that the fluorescence intensity measured by dissolving the sample in ethanol is the strongest; Figure 14To determine the fluorescence intensity ratio between uncontaminated and contaminated samples at different pH levels, the optimal detection pH was explored within the range of 3 to 11. Under strong acid or alkaline conditions, the sample structure was destroyed; the sample solution exhibited the strongest fluorescence intensity at pH 7; excessively high or low pH values affected the sample's fluorescence emission intensity. Simultaneously, Co was added... 2+ After being combined with thiamethoxam, it also showed effectiveness in detecting Co at pH=7. 2+ And the best fluorescence quenching effect of thiamethoxam, when Co is added 2+ The fluorescence of Eu@ZIF-8-NH2 was significantly quenched after the addition of thiamethoxam, exhibiting a turn-off response. Furthermore, the fluorescence intensity remained relatively stable after 1 minute. Figure 15 , 16 As shown, it has a fast response time.
[0082] Depend on Figure 12 It can be seen that in the 550–750 nm range, Eu@ZIF-8-NH2 mainly has emission peaks at 592 nm, 615 nm, and 699 nm, which correspond to... 5 D0→ 7 F1 5 D0→ 7 F2 5 D0→ 7 F4, with the strongest fluorescence intensity at the emission peak at 615 nm, belongs to the 4f-4f transition. Figure 13 It is known that the Eu@ZIF-8-NH2 structure is destroyed in water and N,N-dimethylformamide solvent, resulting in very low fluorescence intensity of the corresponding emission peak, and essentially no fluorescence.
[0083] Experimental Example 7: Fluorescent Titration Experiment
[0084] Preparation of different concentrations of Co 2+ Solution (0~203μmol·L) -1 ) and thiamethoxam (THI) solution (0–112 μmol·L -1 Then prepare a Eu@ZIF-8-NH2 solution of the same concentration (0.5 mg·mL⁻¹). -1 After the reaction was complete, the fluorescence intensity of the solution was measured using a fluorescence spectrometer under the previously optimized conditions.
[0085] Based on fluorescence analysis, the detection linear range is calculated using the Stern-Vomer formula, and then the limit of detection (LOD) formula is used to calculate the lowest detection limit for pollutants.
[0086] Stern-Vomer formula: I0 / I=1+K sv [M]
[0087] LOD calculation formula: LOD = 3SD / K
[0088] Where I0and I are the fluorescence intensity of the fluorescent probe before and after the addition of pollutants, M is the concentration of the detected pollutants in the detection solution (μmol·L -1 ), K sv is the parameter of the Stern-Vomer equation, usually 3, K is the slope of the linear fitting of the Stern-Vomer equation, and SD is the standard deviation of 10 blank samples.
[0089] Under the optimal detection conditions, the Eu@ZIF-8-NH2 was used as a fluorescent probe to detect Co 2+ and thiamethoxam (THI) in water, a series of fluorescence titration experiments were carried out and the response relationship was established. As Figure 17 , 18 , with the increase of the concentration of Co 2+ and thiamethoxam added, the fluorescence intensity of Eu@ZIF-8-NH2 at 592 nm, 615 nm and 699 nm decreased significantly. The experimental data were fitted by the Stern-Volmer equation Figure 19 , 20 ), in the range of 0-203 μmol·L -1 of Co 2+ concentration and in the range of 0-112 μmol·L -1 of thiamethoxam concentration, the fluorescence intensity change of the probe material showed a linear relationship (R 2 = 0.996). According to the formula calculation method, the minimum detection limit (LOD) of Co 2+ and thiamethoxam was 0.127 μmol·L -1 and 0.0934 μmol·L -1 , respectively. The fluorescence titration results showed that the prepared Eu@ZIF-8-NH2 had excellent fluorescence detection performance for Co 2+ and thiamethoxam. As shown in Table 3, compared with some existing fluorescent probes, the method had better detection method.
[0090] Table 3 Comparison of Eu@ZIF-8-NH2 with other fluorescent probes
[0091]
[0092] Test Example 8: Selectivity and Anti-interference experiment
[0093] In the experiment, we first precisely prepared the interfering solution, setting its concentration to four times that of the contaminant. Next, the prepared interfering solution was rapidly added to the fluorescent probe system, followed by 10 minutes of sonication. This was done to ensure sufficient contact and rapid reaction between the interfering substance and the fluorescent probe, thereby ensuring the accuracy of the experimental data. After treatment, the degree of fluorescence quenching in each system was measured. By comparing the differences in quenching caused by different interfering substances, the selectivity of the fluorescent probe could be determined.
[0094] Furthermore, to simulate more realistic complex environments, a mixed system in which pollutants and interfering substances coexist was constructed. Specifically, an interfering substance solution, at four times the concentration of the pollutants, was added to the system already containing them. After addition, the solution was sonicated for 10 minutes to ensure homogeneous mixing. Finally, the fluorescence quenching degree of the fluorescent probe in this mixed system was measured and compared with a pollutant probe system without added interfering substances. This method allows for the evaluation of the probe's anti-interference capability when detecting target pollutants in real-world complex environments.
[0095] Considering Co 2+ Compared to the environment in which thiamethoxam is used as a fluorescent probe, a series of interfering solutions that might cause detection interference were prepared for comparison to test whether this probe possesses excellent selectivity and anti-interference ability. The solution was prepared at an interfering concentration of Co. 2+ At a concentration four times that of thiamethoxam, systematic fluorescence spectroscopy revealed that, in addition to Co 2+ Besides thiamethoxam causing fluorescence quenching of Eu@ZIF-8-NH2, Figure 21 Other substances (Zn) 2+ Ni 2+ Na + Mn 2+ Mg 2+ K + Ca 2+ (AMP, PMG) had little effect on its fluorescence intensity, with no significant disturbance. In anti-interference detection ( Figure 22 Even with a 4-fold concentration of interfering substances, adding Co... 2+ The fluorescence intensity of the probe was still quenched after reacting with thiamethoxam. These results indicate that Eu@ZIF-8-NH2 is effective against Co. 2+ The fluorescence detection of thiamethoxam exhibits strong selectivity and anti-interference ability.
[0096] The synthesized probe was used to detect Co in actual water samples. 2+ The feasibility of this detection method was evaluated using the spiked recovery method for the detection of thiamethoxam and other pyramidal compounds. The results are shown in Tables 4 and 5, within the range of 0–50 μmol·L⁻¹. -1 Co2+ The recovery rate was 96.52%~103.77% with the relative standard deviation (RSD) ≤5.76% under the addition of the scalar; the recovery rate was 95.56%~100.81% with the relative standard deviation (RSD) ≤6.12% under the addition of 0~50 μmol·L -1 of thiamethoxam. The results showed that the detection method had good practical application effect.
[0097] Table 4 Detection of Co 2+ in the water sample of Fangming Lake
[0098]
[0099] Table 5 Detection of thiamethoxam (THI) in the water sample of Fangming Lake
[0100]
[0101] Conclusion:
[0102] (1) The Eu@ZIF-8-NH2 fluorescent material was successfully synthesized by post-modification method with rare earth metal europium, terephthalic acid and amino ZIF-8 as raw materials. ZIF-8 and ZIF-8-NH2 both showed dodecahedron morphology with a size of about 70 nm. After loading, the size of Eu@ZIF-8-NH2 increased slightly, and the morphology changed slightly, and the element was pure without impurities.
[0103] (2) In the process of amination and loading, the crystal structure of ZIF-8 was not destroyed, and Eu@ZIF-8-NH2 retained the characteristic diffraction peaks of ZIF-8.
[0104] (3) The optimal excitation wavelength of Eu@ZIF-8-NH2 was 254 nm, at which the fluorescence intensity was the strongest and the red light was emitted. The fluorescence intensity was stable within 0~7 d.
[0105] (4) The optimal conditions for detecting Co 2+ and thiamethoxam in water by Eu@ZIF-8-NH2 were as follows: the concentration was 0.5 mg·mL -1 , the solvent was ethanol, and the pH was 7. Under these conditions, Eu@ZIF-8-NH2 showed rapid response to Co 2+ and thiamethoxam, and the fluorescence intensity was basically stable after 1 min of adding the target substance. The linear concentration detection range of Eu@ZIF-8-NH2 for Co 2+ and thiamethoxam was 0~203 μmol·L-1 and 0~112 μmol·L-1, respectively, and the linear relationship was R 2= 0.996; the lowest detection limit (LOD) was 0.127 mol L-1 and 0.0934 mol L-1, respectively. Compared with the existing part of the fluorescent probe, the Eu@ZIF-8-NH2 prepared in the present study has better detection performance. In the selectivity and anti-interference test of a variety of possible interferents, the fluorescent probe has good selectivity and anti-interference ability.
[0106] (5) In the spiked recovery experiment of the actual water sample, there is higher stability and detectability, and it has practical application ability, and can be used as a Co 2+ and thiamethoxam pollution water quantitative analysis of a reliable method.
[0107] In summary, the Eu@ZIF-8-NH2 fluorescent material prepared in the present embodiment has good structural stability, excellent fluorescence performance, high sensitivity and strong anti-interference ability, and can be used for detecting Co 2+ and thiamethoxam in water, and has great application potential, and provides a new effective material and detection method for water pollution detection.
[0108] The above is only a preferred embodiment of the present application, and therefore cannot limit the scope of the present application, that is, equivalent changes and modifications made according to the scope and content of the present patent should still be within the scope of the present application.
Claims
1. A method for preparing a ZIF-8 fluorescent composite material based on coordinating europium ions and post-modification, characterized in that: The method comprises: S1: respectively dissolving zinc nitrate hexahydrate, 2-methyl imidazole and 2-amino benzimidazole in methanol to form solution A and solution B, after ultrasonic treatment, the B solution is quickly added to solution A and stirred, stirring at room temperature for 4h, then centrifugal washing with methanol, drying in a blast drying oven at 55-65℃ for 11-13h, then transferring to a vacuum drying oven at 140-160℃ for activation for 11-13h, and grinding to obtain an amino-functionalized ZIF-8 composite material; S2: dissolving the amino-functionalized ZIF-8 composite material prepared in step S1 and europium nitrate hexahydrate in methanol, then adding terephthalic acid thereto, stirring at room temperature for 5-7h, centrifugal treatment, washing with methanol, drying in a blast drying oven at 55-65℃ for 24h, and grinding to obtain a ZIF-8 fluorescent composite material based on coordination of europium ions for post-modification.
2. The method for preparing the coordination europium ion-based post-modified ZIF-8 fluorescent composite material according to claim 1, characterized in that: In the step S1, the molar mass ratio of 2-methyl imidazole and 2-amino benzimidazole is 54:
1.
3. The method for preparing the coordination europium ion-based post-modified ZIF-8 fluorescent composite material according to claim 1, characterized in that: In the step S1, Zn 2+ The molar mass ratio of 2-methylimidazole and 2-aminobenzimidazole is 10:50-55:1-1.
5.
4. The method for preparing the coordination europium ion-based post-modified ZIF-8 fluorescent composite material according to claim 1, characterized in that: In the step S2, Eu 3+ and the mass ratio of the amino-functionalized ZIF-8 composite material is 1:2.5-3.
5. The method for preparing the coordination europium ion-based post-modified ZIF-8 fluorescent composite material according to claim 1, characterized in that: In the step S2, Eu 3+ and terephthalic acid is 2:
3.
6. The method for preparing the coordination europium ion-based post-modified ZIF-8 fluorescent composite material according to claim 1, characterized in that: In the step S2, the mass ratio of terephthalic acid to the amino-functionalized ZIF-8 composite material is 5-5.5:
1.
7. A coordination Eu3+ ion post-modified ZIF-8 fluorescent composite material, characterized in that: The ZIF-8 fluorescent composite material based on coordination of europium ions for post-modification is prepared by the preparation method of the ZIF-8 fluorescent composite material based on coordination of europium ions for post-modification in any one of claims 1-6.
8. Application of a coordination europium ion post-modified ZIF-8 fluorescent composite material in water body detection, characterized in that: The coordination-based europium ion post-modified ZIF-8 fluorescent composite material is used for detecting Co-containing water 2+ water bodies and thiamethoxam.
9. The application of the coordination Eu3+ ion post-modified ZIF-8 fluorescent composite material in water detection according to claim 8, characterized in that: Disperse the ZIF-8 fluorescent composite material based on coordination of europium ions for post-modification in an ethanol solution, and ultrasonic treatment to obtain a uniformly dispersed suspension.
10. The application of the coordination Eu3+ ion post-modified ZIF-8 fluorescent composite material in water detection according to claim 9, characterized in that: The concentration of the ZIF-8 fluorescent composite material based on coordination of europium ions for post-modification is 0.5mg / mL.